Improving Mathematics Learning Outcomes Through Cooperative Learning Model Assisted by Media Dakota FPB and KPK - Banatul Khomsah; Saeful Imam Al Makky; Wahyu Purwasih; Siti Sarah (Jurnal Sekolah Dasar, 2023)
This research was conducted with the aim of improving learning outcomes in mathematics on the subject of FPB and KPK, in class IV students of MI Ma'arif Nu Kedungrandu for the 2022/2023 academic year using the STAD cooperative learning model assisted by dakota media. This type of research is classroom action research using the Kemmis and Mc Taggart model. The research subjects were all fourth grade students at MI Ma'arif Nu Kedungrandu in 2022/2023, consisting of 11 students, 8 boys and 3 girls. The object of this research is the results of learning mathematics on the subject of FPB and KPK on students. Data collection was obtained by the observation method and the test method to measure learning outcomes. The results showed that the class average score in cycle I was 82.6 with a weight of easy questions and a percentage of completeness of 80%, in cycle II the class average was 71 with a weight of difficult questions and a percentage of learning completeness of 80%. This research was said to be successful because 8 out of 10 students who took part in the action got a higher score equal to the specified KKM score. So it can be concluded that the STAD cooperative learning model assisted by dakota media can improve learning outcomes in mathematics on the subject of FPB and KPK in class IV students of MI Ma'arif Nu Kedungrandu in 2022/2023.